PARTNERSHIPS SYSTEM ANALYSIS IN IMMUNIZATION PROGRAM BASED ON THE ROLE OF FORCES THE VILLAGE, MIDWIFE VILLAGE, AND SOCIETY - Arifada, Aqsha Yuldan; Rochmah, Thinni Nurul (Jurnal Administrasi Kesehatan Indonesia, 2015)
ABSTRACTÂ Sumenep regency as the most eastern districts in the region Madura have not been able to meet the target of Universal Child Immunization (UCI) coverage in accordance with the Minimum Service Standards (SPM) Indonesian government. Application of the village partnership system is expected to increase the scope of UCI in the village. This research is aimed to analyze the inputs, processes, and outputs the village partnership system is based on the role of village officials, village midwives, and society. This study uses observational descriptive with cross sectional design. Samples were collected using stratified random sampling method consist of the villages, midwives, and community groups. The result showed that the majority of village officials, midwives, and community groups unoptimal in partnership system in the village, so the need to improvements to the village partnership system is good an solid. There was no significant effect of the variables role of village officials and midwives to result UCI village coverage. On community variables, the process of partnership, and the result of partnership, there are several variables that have significant influence. Based on the survey result it can be concluded that the system of partnership in the area Puskesmas do not use the integrated partnership model, but using a network model of partnership.Keywords: community development, immunization, partnership, Universal Child Immunization